DAILY DATA VISUALIZATION OF PLANT III PT PETROKIMIA GRESIK VIA DASHBOARD UP DATE - Devita Salsa Gunawan; Erwan Adi Saputra; Faris Harditya Purnama; Sani Sani (Konversi, 2022)
Dashboard is a visual display, numbers and metrics containing all the data that aims to provide information and help users to make the right and fast decisions based on existing data. From here, the idea of a project Up To Date Dashboard "BODATE" came about. A dashboard designed with the concept of Less Input, More Output. The dashboard will continue to be updated and changed every day based on production data and existing field realizations. This dashboard includes an observation of the performance of achieving the production targets of each unit, realization, stock of raws materials and products as well as consumption of raw materials for each unit. The result of this "BODATE" Up To Date Dashboard is that it overcomes the difficulty of finding relationships between data, and the set of daily report numbers that are constantly changing every day just by turning it into a unique but still efficient data visualization display in terms of time. The purpose of this "BODATE" Up To Date Dashboard is to create fast and efficient data visualization in order to overcome problems that exist in the Department of Production Planning and Energy Management (PPPE) and can be implemented, especially in the Work Unit of Planning and Control (Rendal) Production Plant III PT Petrokimia Gresik.